Eliglustat protects from damage caused by Shiga toxin type 2 in human renal tubular epithelial cells - Sánchez, Diana Soledad (2020)
Shigatoxin-producing Escherichia coli isresponsible for Hemolytic Uremic Syndrome (HUS), a cause of renal failure inchildren. We have previously shown that C-9 and Eliglustat (EG), inhibitors ofglucosylceramide  synthase andglobotriaosylceramide (Gb3), prevent the cytotoxic effects of Shiga toxin type2 (Stx2), in human cortical renal tubular epithelial cells (HRTEC) primarycultures and HK2 cell line. The aim of this work was to evaluate the efficacyof EG, elucidating EG treatments necessary to achieve total protection against Stx2in HRTEC and HK2. Cells were incubated with Stx2 (1 ng/ml, 24 and 72 h) andpre-incubated with or without EG (1-500 nM, 6 and 24 h), followed byco-incubation with same dilutions of EG and Stx2 (24 and 72 h). Total number ofcells stained with Hoechst was counted in microphotographs and compared withcell viability measured by neutral red uptake. Early and late apoptosis andnecrosis was evaluated by annexin V/propidium iodide staining. Tubulogenesis wasevaluated in HRTEC grown on matrigel. Treatment of cells with Stx2significantly decreased cell confluence and viability and the number of cellsattached (p<0.001). In HRTEC, Stx2 increased early and late apoptosis, andnecrosis compared to non-treated cells (p<0.01). Furthermore, Stx2 inhibitedcell aggregation and tubulogenesis on matrigel. HRTEC preincubated with EG (50nM, 24 h or 500 nM, 6 h) totally prevented Stx2 effects on HRTEC measured as cellcount, viability, apoptosis, necrosis and tubulogenesis (p<0.05). Preincubationof HK2 cells with EG (1 nM, 24 h or 10 nM, 6 h) totally prevented Stx2 effectson cell viability and confluence. EG alone did not produce cytotoxic effectsper se. In conclusion, EG protects human renal tubular epithelium against Stx2cytotoxicity being HRTEC more sensitive than HK2. Treatment with EG could be anovel substrate inhibition therapy to neutralize Stx2 action and prevent renal damagein patients with HUS.